Students’ Perception on the Use of Canva as a Presentation Tool: The Study at SMA Srijaya Negara Palembang - Salsabila, Annisa; Amrullah, Amrullah (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
In the context of 21st-century learning, the integration of digital tools is essential to enhance student engagement and academic success. The aim of this study is to investigates students’ perceptions of using Canva as a presentation tool in English language learning at SMA Srijaya Negara Palembang. The research employed a quantitative descriptive method using a closed-ended questionnaire that covered three indicators: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention (BI). The participants consisted of 91 tenth-grade students, and the collected data were analyzed statistically to obtain mean scores and standard deviations on a 7-point Likert scale. The results showed that students’ perceptions were consistently in the “High” category, with mean scores of 5.78 for PU, 5.77 for PEOU, and 5.70 for BI. These findings indicate that students perceive Canva as an effective and easy-to-use tool for classroom presentations and demonstrate a strong intention to continue utilizing it in future academic projects. In conclusion, Canva is recognized as a valuable digital resource that not only supports English language learning but also strengthens students’ presentation skills and enhances their digital literacy, thereby contributing to the development of 21st-century competencies.